(untitled) (Journal Genta Kebidanan, 2024)
Some mothers will experience complications during antenatal visits complaining about the pain that occurs during pregnancy. One of the discomforts most frequently reported by pregnant women is nausea and vomiting in the first trimester of pregnancy. This study aims to determine whether there is an effect of essential oil aroma therapy on nausea and vomiting during pregnancy. The method used in writing this article is a review of research results related to complementary therapy in reducing or reducing nausea and vomiting during pregnancy. From the results of the literature review, it was found that the use of aromatherapy or essential oils greatly influences the intensity of reducing nausea and vomiting in pregnant women, including aromatherapy, lemon aromatherapy (Citrus Lemon), Peppermint aromatherapy, Lavender aromatherapy, Orange aromatherapy, Ginger aromatherapy (Zingiber officinale), Grapefruit aromatherapy ( Lemon Paradisi), and lemongrass aromatherapy. It is hoped that the use of aromatherapy as a complementary treatment for nausea and vomiting in pregnant women in health facilities.